Efektivitas Durasi Intervensi Terapi Wicara terhadap Peningkatan Kemampuan Artikulasi pada Anak Hearing Impairment di SLB YRTRW Surakarta - Putri, A.Tenri Nuraliyah; Tirtawati, Dewi; Siswanto, Arif (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Hearing loss is the partial or complete loss of the ability to hear sound in one or both ears. The problem of hearingimpaired children is a communication problem, their inability to communicate has a wide impact, both on language skills, reading, writing and social adaptation and academic potential. Articulation disorders are disorders that arise due to the formation of speech sound errors reviewed from location, force, speed, time, and pressure. Duration includes an overview of how long an individual spends time on various purposes. This means that the duration of therapy can be measured through how long the therapist spends in conducting the therapy program. Objectives: To determine the effectiveness of the duration of speech therapy intervention on improving articulation in children with hearing impairment in SLB YRTRW Surakarta. Methods: This study is a quantitative study. The research design was carried out by experimental method, namely a two-group pretest-post test design. The sampling technique in this study is the total sampling and the number of samples taken by 10 respondents. The data were analyzed by univariate and bivariate analysis. The statistical test used is Mann-Whitney. Results: This study received a p-value of .011 which means that this value is smaller than p = 0.05 so it can be concluded that there is a real difference between the results of the post-test of 30 and 45 minutes of therapy, so that the duration of 45 minutes of therapy is more influential than 30 minutes in improving articulation in hearing impaired children. Conclusion: The longer the duration of the intervention given, the more likely it is to have the potential to improve the articulation of hearing impairment children. Keywords: Articulation, Duration of Intervention, Hearing Impairment